Intravital imaging-based analysis tools for vessel identification and assessment of concurrent dynamic vascular events - Naoki Honkura (Nature Portfolio, 2018)
Different stimuli can induce dynamic changes in blood flow velocity, vessel diameter and permeability. Here the authors develop a multi-photon microscopy-based image analysis tool allowing the identification of vessels and the assessment of rapid changes in large vascular networks.